(5,15-Dianthracen-9-yl-10,20-dihexylporphyrinato)nickel(II): a planar nickel(II) porphyrin - Mathias O. Senge; Mia Davis (Acta Crystallographica Section E, 2010)
The title compound, [Ni(C60H52N4)], is an example of a meso tetrasubstituted nickel(II) porphyrin with both meso aryl and alkyl residues. The molecule exhibits a planar macrocycle with an average deviation of the 24 macrocycle atoms from their least-squares plane (Δ24) of 0.01 Å and an average Ni—N bond length of 1.960 (2) Å. The NiII atom lies on a center of inversion. The structure presents a rare example for a planar nickel(II) porphyrin, as meso-substituted nickel(II) porphyrins with either only meso-aryl or with meso-alkyl residues typically exhibit a ruffled conformation.